PATOMAN SEBAGAI DESA KEBANGSAAN DI KABUPATEN BANYUWANGI - Bayu Indra Permana; Agus Mursidi (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTIdentification of the emergence of a nationality village in Patoman village needs tobe done, this is done because Patoman village has the potential of various types ofheterogeneous communities in terms of religion, culture or ethnicity. So it needs tobe traced and further studies need to be done on the identification of villages that areincluded in the elements of nationalism village. This becomes important and servesas a basis for reference to the grouping of villages that have an element of pluralismand will later be designated as a nationality village. On the other hand can be usedas a reference and input by local governments in providing policies regarding theexistence of a nationality village. Besides that, support from the local governmentrelated to the promotion of the potential / superiority of culture, ethnicity, villagesand regions in Banyuwangi is very intensively carried out, as evidenced by the manyfestivals that are held and scheduled every one year. This research is to identifyvillages that have the potential to become nationality villages in which there arevarious criteria or elements that have been fulfilled, one of which is the compositionof religion, culture, ethnicity and the form of tolerance that is maintained andsustainability, from the results of its study can be used as foothold for policy makers,especially the Banyuwangi local government and related ministries. This researchuses a qualitative approach with a case study design and uses a phenomenologicalperspective. The selection of respondents using snowball sampling, namely thevillage and district government in Blimbingsari, community leaders, religiousleaders, Banyuwangi National Mixing Forum and cultural figures. From the resultsof the research it can be seen that the tolerance value of patoman society and itsdiversity is very close and very good in community relations can be seen from theimplementation of mutual values and religious tolerance.Keywords: Identification, village, patoman nationality